STANISLAV VISPYANSKIY IN COMPARATIVISTSCIH MEASURINGS OF UKRAINIAN EXPLORER - Hmeliuk, M. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Review on monografiy of Miroslava Meditska"Creation of Stanislav Vispyansky and Ukrainian literature of the end of XIX - beginning of XX age: reception and tipologiya". - Ivano-Francovsk, 2008. – 316 s.